Component-Resolved Diagnosis of American Cockroach (Periplaneta americana) Allergy in Patients From Different Geographical Areas - Wangorsch, Andrea; Jamin, Annette; Eichhorn, Stephanie; Pablos, Isabel; Sharma, Swati; Schweidler, Bettina; Kastner, Bianca; Wildner, Sabrina; Saloga, Joachim; Führer, Frank; Reyna Orozco, Reinaldo Rafael; Sherkat, Roya; et al. (Frontiers in Allergy, 2021)
Background: Manifestation of respiratory allergy to American cockroach (Periplaneta americana) is prominent in the subtropical and tropical areas. However, co-existing perennial indoor inhalant allergies frequently compromise clinical diagnosis of cockroach allergy, and the analysis of sensitization pattern is limited by the lack of Periplaneta allergens widely available for component-resolved diagnostics (CRD). Objective: To evaluate a collection of previously described recombinant Periplaneta allergens for CRD in cockroach allergy. Methods: A panel of nine recombinant Periplaneta allergens (Per a 1–5, 7–10) was generated, purified, and subjected to physicochemical characterization by applying circular dichroism (CD) spectroscopy, dynamic light scattering (DLS), amino acid (AA) analysis, and mass spectrometry (MS). Patients (n = 117) from India, Korea, Venezuela, and Iran, reporting perennial respiratory indoor allergies with IgE sensitization to cockroach (P. americana and/or Blattella germanica), were included. The sensitization profile was monitored by the experimental ImmunoCAP testing. Results: ImmunoCAP testing confirmed IgE sensitization to Periplaneta and/or Blattella extract in 98 of 117 patients (r = 0.95). Five out of 117 patients were sensitized to only one of the two cockroach species. Within the whole study group, the prevalence of sensitization to individual allergens varied from 4% (Per a 2) to 50% (Per a 9), with the highest IgE values to Per a 9. Patients from four countries displayed different sensitization profiles at which Per a 3 and Per a 9 were identified as major allergens in India and Korea. Periplaneta-derived lipocalin and myosin light chain were characterized as new minor allergens, designated as Per a 4 and Per a 8. Periplaneta extract showed higher diagnostic sensitivity than all individual components combined, suggesting the existence of allergens yet to be discovered. Conclusion: Utilization of a panel of purified Periplaneta allergens revealed highly heterogeneous sensitization patterns and allowed the classification of lipocalin and myosin light chain from Periplaneta as new minor allergens.